The Modern Grievance Procedure in the United StatesThe Modem Grievance Procedure in the United States, by LewinDavid and PetersonRichard B. Westport, CT: Quorum Books. 1988. 304 pp., $45.00, hardback. - Kelly, Eileen P. (Academy of Management Review, 1990)
The article presents a review of the book ?The Modern Grievance Procedure in the United States,? by David Lewin and Richard B. Peterson.